Optimalisasi Media Sosial Youtube sebagai Media Berwirausaha - Mahiruna, Adiyah; Rowiyani; Ngatimin; Rahmat Riansyah; Arya Yuda Ega Wardana (Jurnal Atma Inovasia, 2024)
YouTube is a website that allows people to upload and exchange videos. YouTube is an effective social media platform for companies to introduce their products through video content. YouTube is developing into an effective tool for business. YouTube offers live broadcasts of product or service demos, YouTubers can record and post videos about the offers they want, and these offers can attract clients. With millions of videos produced every day, YouTube social media has a good chance of getting videos seen, so you have the opportunity to succeed in online business using YouTube media. Another advantage of social media is that YouTube can improve their marketing techniques and gain a better understanding of their audience by using the analytical tools that YouTube offers. Therefore, YouTube serves as an important tool for doing business online, besides being a place to share YouTube videos. Considering the background information provided, optimizing YouTube social media aims to motivate and improve the abilities of Dawis mothers who want or are currently entrepreneurship in utilizing YouTube as an online business medium. Mrs. Dawis can improve viewers' understanding and retention of knowledge by producing more visually interesting informational material or videos on YouTube. People are more likely to understand and retain knowledge when it is presented on YouTube in an original and engaging way. Therefore, optimizing social media is needed to help Dawis mothers develop their capacity to produce interesting and successful YouTube videos. Thus, Dawis women can use YouTube as a platform for online commerce and entrepreneurship more effectively. This community service aims to optimize the use of YouTube social media as an entrepreneurial tool for Dasa Wisma (Dawis) women in Amposari Village, Pedurungan District, Semarang City. This program was implemented by the Community Service (PKM) team from the Muhammadiyah Semarang Institute of Statistics and Business Technology in March 2024. This activity included theoretical and practical training involving 25 participants from various RTs in the village. The methods used include interviews, discussions, lectures, and questions and answers, with the aim of exploring online business ideas and improving the entrepreneurial spirit of participants